2021
DOI: 10.1186/s12944-021-01538-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of a reduction in the level of high-density lipoprotein-cholesterol in patients with non-small-cell lung cancer undergoing radical resection and adjuvant chemotherapy: a retrospective observational study

Abstract: Background Cancer patients often exhibit chemotherapy-associated changes in serum lipid profiles, however, their prognostic value before and after adjuvant chemotherapy on survival among non-small-cell lung cancer (NSCLC) patients is unknown. Methods NSCLC patients undergoing radical resection and subsequent adjuvant chemotherapy from 2013 to 2017 at Sun Yat-sen University Cancer Center were retrospectively reviewed. Fasted serum lipid levels were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…A retrospective study of Ma et al [ 25 ] proved the association of the preoperative upregulated TG and downregulated HDL-C with an unfavorable prognosis in patients who died from NSCLC. Furthermore, Luo et al [ 26 ] reported that relatively high HDL-C before adjuvant chemotherapy were independent prognostic factors with longer disease-free survival for NSCLC patients. Meanwhile, Lv et al [ 30 ] revealed that the decrease in HDL-C level could indicate liver dysfunction caused by adjuvant chemotherapy in NSCLC, which partly supported the predictive significance of TG/HDL-C for patient prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study of Ma et al [ 25 ] proved the association of the preoperative upregulated TG and downregulated HDL-C with an unfavorable prognosis in patients who died from NSCLC. Furthermore, Luo et al [ 26 ] reported that relatively high HDL-C before adjuvant chemotherapy were independent prognostic factors with longer disease-free survival for NSCLC patients. Meanwhile, Lv et al [ 30 ] revealed that the decrease in HDL-C level could indicate liver dysfunction caused by adjuvant chemotherapy in NSCLC, which partly supported the predictive significance of TG/HDL-C for patient prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the correlation of TG and HDL-C levels with cancer prognosis is not well characterized, especially in the context of NSCLC. In only limited studies, serum TG or HDL-C was linked to the prognosis of NSCLC patients [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Histologic review of sacrificed rats showed evidence of myofibrillar loss and vessel wall thickening in those treated with cisplatin but not oxaliplatin, but these results have not been replicated in human studies. In clinical studies in humans, an adjuvant combination regimen primarily composed of cisplatin, carboplatin, and nedaplatin was found to be associated with increased levels of TC, LDL, HDL, and TG at the end of the treatment period ( 76 ). However, in two other studies in human subjects, no changes in plasma cholesterol were seen shortly after cisplatin therapy ( 77 ) nor after >5 year follow up ( 74 ).…”
Section: Cytotoxic Therapy and Ascvd Riskmentioning
confidence: 99%
“…Importantly, patients with active neoplastic disease are most often excluded from randomized controlled trials [ 3 ]. The ESC expert document on cancer treatments and cardiovascular toxicity also does not address the issue of optimal lipid-lowering treatment in patients with active cancer and MI [ 5 ], despite surprisingly reported lower levels of low-density lipoprotein (LDL) cholesterol in patients with MI and cancer than non-cancer ones (risk ratio 0.87, 95% confidence interval (CI) 0.85–0.89) [ 6 ] and the fact that neoplastic treatment changes the lipid profile to pro-atherogenic [ 7 , 8 , 9 ]. This problem is especially urgent since statins, due to their pleiotropic effects, constitute another potentially useful anticancer pharmacotherapy [ 10 ].…”
Section: Introductionmentioning
confidence: 99%